Faktor yang Mempengaruhi Akuntabilitas Laporan Keuangan Daerah dengan Kualitas Informasi sebagai Variabel Mediasi - Aditya Paramarta, I Wayan; Ariyanto, Dodik (E-Jurnal Akuntansi, 2021)
The research aims to analyze the factors that influence the accountability of local financial statements. The population in this study is the head and staff of the sub-division of accounting or in the central government of Badung Regency. The sampling technique in this research is to use the non probabilty sampling method with saturated sampling technique. The research sample is 29 Regional Organization of Badung Regency. The analysis technique in this study uses the path analysis technique. The results of the study are that the internal control system has a positive and significant effect on regional financial accountability and information quality. Human resource competence has a positive and significant effect on regional financial accountability and information quality. The quality of information has a positive and significant effect on regional financial accountability. Information quality is able to mediate the influence of internal control systems and resource competencies on regional financial accountability. Keywords: Accountability; Information Quality.